(untitled) (Stamford Journal of Microbiology, 2017)
Present study attempted to detect the prevalence of contaminating microorganisms in 10 categories of local market apple samples commonly consumed in Dhaka city, Bangladesh. A significant number of total viable bacteria were quantified up to 106 cfu/g in these samples. Staphylococcus spp. was the predominant isolate within a range of 1.0×104 3.2×106cfu/g whereas Escherichia coli, Klebsiella spp., Salmonella spp., Shigella spp., Pseudomonas spp. and Vibrio spp. were also quantified. Fungal contamination (within the range of 105 cfu/g 107cfu/g) was also observed. Alarmingly most of the bacterial isolates present in the samples were proved to be multi-drug resistant. Antibacterial activity of the samples was tested against some common bacterial isolates but was found to be ineffective. Stamford Journal of Microbiology, Vol.6(1) 2016: 11-15